The brain and mathematics - D'Arcangelo, Marcia; Wuzburg, Gerardine; Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2001)
The purpose of this video series is to help schools, districts, and individual teachers consider how understanding brain funtion can lead to improved teaching and learning of mathematics for all children. The program can be used to introduce principals, supervisors, district curriculum developers, parents, students teachers, and others to the purpose and concepts of brain-compatible instruction
tape 1. Making number sense (41 min.) -- tape 2. Classroom applications (27 min.)
Title from title screen
Editor, Alison Spray ; associate producer, Dana Sheets ; camera, Gary gayboy, Gary Griffin ; sound, Robert Silverthorne, Dennis Towns, Dwayne Dell
Keywords: Teachers -- Training; Mathematics -- Study and teaching; Brain -- Research; Mathematical ability